Corrosion inhibition of mild steel using poly (2-ethyl -2-oxazoline) in 0.1M HCl solution. Issue 11 (November 2020) - Mathew, Zachariah Pulluparampil; Rajan, Keerthi; Augustine, Cyril; Joseph, Bincy; John, Sam
Abstract: Effective inhibition of metallic corrosion to prevent its consequent loss is one of the serious apprehensions for industries in the modern world. This paper analyses the application of poly(2-ethyl-2-oxazoline) (PEOX) as an effective inhibitor of corrosion, when it is made to be in contact with the surfaces of mild steel (MS). The sustainability of MS against corrosion in 0.1 M Hydrochloric acid solution in the presence of known concentration of PEOX is assessed by potentiodynamic polarization (PDP) measurements, linear polarization studies (LPR), and electrochemical impedance spectroscopy (EIS). It was observed that PEOX behaves as better inhibitor for mild steel corrosion in 0.1 M HCl solution and it show enhanced inhibition efficiency (IE%) 79% at a concentration of 50 ppm. The polarization experiments indicated that addition of PEOX in concentrations varies from 25 ppm to 50 ppm induces a decrease of both cathodic and anodic currents densities. Also, the micrographs recorded by the Scanning Electron Microscopy confirm that molecules of PEOX act as corrosion inhibitors for the surfaces of MS in 0.1 M HCl. The stability of the MS surface in a corrosion-prone environment is traced by measuring the contact angles of water droplets placed on the MS surface, to quantify the extent of deterioration, if any, due to corrosion. The results presented here show that the compound PEOX performs as a mixed-type inhibitor against corrosion at the MS surface in acidic medium. Theoretical studies based on the electronic structure of PEOX in aqueous medium also support its performance as a successful corrosion-inhibitor. Abstract : Materials Science; Materials Chemistry; Electrochemistry; Physical Chemistry; PEOX; Mild Steel; Corrosion; Contact Angle Measurement; EIS.